2006
DOI: 10.4161/cc.5.15.3112
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Fibroblasts in Cancer: A Novel Tumor-Promoting Cell Type

Abstract: Tumors are highly complex tissues composed of neoplastic cells and, in the case of carcinomas, stromal cell compartments containing a variety of mesenchymal cells, notably fibroblasts, myofibroblasts, endothelial cells, pericytes, and a variety of inflammatory cells associated with the immune system. Fibroblasts and myofibroblasts often represent the majority of the stromal cells within various types of human carcinomas, yet the specific contributions of these cells to tumor growth are poorly understood. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
581
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 737 publications
(606 citation statements)
references
References 38 publications
10
581
0
9
Order By: Relevance
“…19,20 Adaptions in the surrounding stroma, in part mediated by macrophages recruited to the tissue around tumors, 20 such as growth of the supporting vasculature and tissue remodulation are probably necessary for subsequent tumor growth and metastasis. 19 -21 Such responses in tumor-adjacent nonmalignant tissues are morphologically similar to those seen around wounds, 8,51 and the gene expression in the normal rat prostate tissue surrounding an implanted AT-1 prostate cancer is similar to that in wounding and inflammation (Adamo et al, unpublished data). Tumors apparently are able to stimulate HA synthesis, either directly or through recruiting inflammatory cells, in surrounding cells and as the tumor expands previously nonmalignant stroma becomes integrated into the tumor stroma, probably explaining why the tumor stroma and nonmalignant tissue stroma show similar changes in HA staining.…”
Section: Discussionmentioning
confidence: 91%
“…19,20 Adaptions in the surrounding stroma, in part mediated by macrophages recruited to the tissue around tumors, 20 such as growth of the supporting vasculature and tissue remodulation are probably necessary for subsequent tumor growth and metastasis. 19 -21 Such responses in tumor-adjacent nonmalignant tissues are morphologically similar to those seen around wounds, 8,51 and the gene expression in the normal rat prostate tissue surrounding an implanted AT-1 prostate cancer is similar to that in wounding and inflammation (Adamo et al, unpublished data). Tumors apparently are able to stimulate HA synthesis, either directly or through recruiting inflammatory cells, in surrounding cells and as the tumor expands previously nonmalignant stroma becomes integrated into the tumor stroma, probably explaining why the tumor stroma and nonmalignant tissue stroma show similar changes in HA staining.…”
Section: Discussionmentioning
confidence: 91%
“…This not only fulfills a spatial requirement for tumor growth, but also allows the tumor to attract various cells from the microenvironment that provide favorable conditions for tumor growth, such as endothelial cells, fibroblasts and macrophages (Bingle et al, 2002;Orimo and Weinberg, 2006). Previously it has been shown that various types of human cancer cells form invadopodia.…”
Section: Reduced Expression Of Tks5 In Src-transformed Nih-3t3 Cells mentioning
confidence: 97%
“…Clearly it is important to identify the factors that help to enhance the growth and "health" of tumors and also contribute to their further distribution. Considerable evidence now suggests that chemokine signaling, and CXCR4 signaling in particular, can contribute to both of these phenomena (Kucia et al, 2005a;Orimo et al, 2005;Orimo and Weinberg, 2006). First SDF-1 is produced by many tumors where it can have autocrine growth promoting effects on the developing tumor and also enhance the growth of blood vessels that are important for further tumor growth and development indicating a key role for CXCR4 (or possibly CXCR7).…”
Section: Chemokine Signaling In Diseasementioning
confidence: 99%